Potential of Ethanol and N-Hexane Fractions of Petai (Parkia Speciosa Hassk.) Leaf Extract as Antibacterials against Staphylococcus aureus and Propionibacterium acnes with Bioautography - Refmidawati, Refmidawati; Masneli Masri; Adinda Andini (RADINKA JAYA UTAMA PUBLISHER, 2023)
This research is motivated by the ethanol fraction and n-hexane fraction of petai leaves have anti-bacterial activity against the growth of Staphylococcus aureus and Propionibacterium acnes with bioautography and what compounds act as antibacterial agents against the growth of S. aureus and P. acnes. The aims (1) to prove the antibacterial activity of the ethanol fraction and n-hexane fraction of Petai leaves in the growth of Staphylococcus aureus and Propionibacterium acne (2) to obtain active compounds from the ethanol fraction and n-hexane fraction which had antibacterial activity against the growth of Staphylococcus aureus and Propionibacterium acnes. The method used in this research is pure experimental carried out by the Pharmaceutical Natural Material Chemistry Laboratory for the extraction and fractionation process. The design method in this study used a completely randomized design (CRD) with 3 (three) repetitions. The results obtained in this study were (1) Ethanol fraction of Petai leaves had antibacterial activity against S. aureus and P. acnes. In contrast, the n-hexane fraction of petai leaves had no antibacterial activity. (2) The ethanol fraction of petai leaves was proven to contain flavonoids, alkaloids, and saponins and the class of active compounds that were most effective at inhibiting S. aureus bacteria in the ethanol fraction of petai leaves were alkaloid compounds. In contrast, the active compounds p acnes were alkaloids and saponins with a value of Rf 0 .52 and 0.61. Conclusion: The ethanol fraction of Petai leaves contains flavonoids, alkaloids, and saponins, which effectively inhibit S. aureus and P. acnes bacteria.